Geology of Almería – semi-desert zone of Spain - Labus, Małgorzata (Geotourism/Geoturystyka, 2018)
The paper presents selected geosites in the arid Province of Almería (Andalucia, Spain). This region is famous of exceptional, climatic and environmental conditions as well as of geological features. The three geological units are distinguishable in the Almeria: strongly folded and deformed metamorphic rocks of the Iberian Massif, Alpine mountain chain of the Betic Cordilliera and intra-montane basin filled with Neogene sediments. The most interesting is the region of Cabo de Gata-Nijar Natural Park, where the Miocene volcanic domes and calderas can be seen in the field. There is also a variety of exposed, igneous and sedimentary rock, as well as the relics of gold mine in Rodalquilar.